The population structure of Ukraine in relation to the phenylthiocarbamide sensitivity - O.V. Filiptsova (Egyptian Journal of Medical Human Genetics, 2015)
Background: The taste sensitivity to phenylthiocarbamide (PTC) is one of the classical genetic markers in human studies. PTC is of great interest from the medical point of view since a number of associations of the taster status with human diseases have been found. The aim of our study was to evaluate the population structure of Ukraine in relation to PTC sensitivity. Methods: The study involved 533 people (78 males and 455 females) aged from 16 to 25 years. The PTC solution in the concentration of 0.13% was prepared according to the method of Harris and Kalmus. The participants of the study analyzed the taste of the filter paper impregnated with PTC. If the trial subjects tasted PTC as “bitter”, “very bitter”, “bitterish”, the phenotype was defined as a taster. If the trial subject did not taste PTC (“no taste”, “taste of paper”), he/she was referred to a non-taster. Results: The structure of the sample of the Ukrainian population studied in relation to the phenotypic and genotypic frequency associated with the phenylthiocarbamide sensitivity has been studied. It has been shown that in the population there are 22% of those who do not feel the taste of phenylthiocarbamide. Among males there are a few more non-tasters than among females, however, the differences are not significant. The frequency of the dominant and recessive allele of the phenylthiocarbamide sensitivity gene in the sample calculated on the basis of the Hardy–Weinberg equation is generally pT = 0.55 and qt = 0.45, respectively. Conclusions: Frequencies of alleles T and t obtained in the male and female population under research are very close to the frequencies of the same alleles in some populations of India. Data of this study supplement the currently available information in relation to the genetic structure of modern Ukrainian cities.